Soybean genetics, genomics, and breeding for improving nutritional value and reducing antinutritional traits in food and feed - William M. Singer; Yi‐Chen Lee; Zachary Shea; Caio Canella Vieira; Dongho Lee; Xiaoying Li; Mia Cunicelli; Shaila S. Kadam; Mohammad Aamir Waseem Khan; Grover Shannon; M. A. Rouf Mian; Henry T. Nguyen; et al. (The Plant Genome, 2023)
Abstract Soybean [Glycine max (L.) Merr.] is a globally important crop due to its valuable seed composition, versatile feed, food, and industrial end‐uses, and consistent genetic gain. Successful genetic gain in soybean has led to widespread adaptation and increased value for producers, processors, and consumers. Specific focus on the nutritional quality of soybean seed composition for food and feed has further elucidated genetic knowledge and bolstered breeding progress. Seed components are historical and current targets for soybean breeders seeking to improve nutritional quality of soybean. This article reviews genetic and genomic foundations for improvement of nutritionally important traits, such as protein and amino acids, oil and fatty acids, carbohydrates, and specific food‐grade considerations; discusses the application of advanced breeding technology such as CRISPR/Cas9 in creating seed composition variations; and provides future directions and breeding recommendations regarding soybean seed composition traits.